Business plan: Launch of an e-learning platform - Lourenço, Ana Margarida Dias (2022)
This project aims to develop a business plan to launch a digital learning platform. This platform targets students between the 5th and 12th grades, and aims to fill a gap in the market, by offering a differentiated approach than the ones that already exist in Portugal. This is accomplished by allowing students to buy only the necessary contents, and not being obligated to buy the entire curriculum. Moreover, it focuses on teaching Mathematics, the subject with which students struggle the most. This content is going to be fully developed by teachers, private tutors, tutoring centers or schools, that will, in their turn, earn a percentage of the revenue generated by their contents. A questionnaire was administered to understand customers’ expectations regarding digital learning platforms, and help define our strategy. The online platform market is in high demand and growth, together with private tutoring, mainly due to the impact of the Covid-19 pandemic that has accelerated the digital transformation in the education area. Although the market is growing, the significant initial investment required to develop the platform, as well as the limitations imposed by only focusing on mathematics. However, after a financial analysis, we came to the conclusion that this project is financially viable.